1989
DOI: 10.1111/j.1432-1033.1989.tb14506.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide reductase from Pseudomonas stutzeri

Abstract: The oxidation-reduction and spectroscopic properties of various forms of nitrous oxide reductase from Pseudomonas stutzeri were investigated. The high-activity form I of the enzyme (purple, 8 Cu, M , 140000) was reduced by a large variety of cationic, anionic and photochemically generated agents. The blue form I11 was the only product found in these experiments under anaerobic conditions. Reductive (dithionite) and oxidative (ferricyanide) titrations showed that the conversion of the purple form I to the blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
146
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 59 publications
9
146
1
Order By: Relevance
“…Addition of a trace of the mediator dye phenazine methosulphatc, (PMS) (I!$, = +80 mV), speeds up reduction generating a blue form absorbing at 650 nm. This is consistent with earlier reports that reduction of N,OR with sodium dithionite proceeds in 2 kinetic steps, a fast phase followed by a slower phase [4]. The second phase of reduction, catalysed by PMS, gives rise to an isosbestic point at 624 nm in the absorption spectrum.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Addition of a trace of the mediator dye phenazine methosulphatc, (PMS) (I!$, = +80 mV), speeds up reduction generating a blue form absorbing at 650 nm. This is consistent with earlier reports that reduction of N,OR with sodium dithionite proceeds in 2 kinetic steps, a fast phase followed by a slower phase [4]. The second phase of reduction, catalysed by PMS, gives rise to an isosbestic point at 624 nm in the absorption spectrum.…”
Section: Resultssupporting
confidence: 93%
“…2). The spectra of the oxidised and fully reduced forms agree well with those reported previously [3,4], the 7-line hyperfine structure of the oxidised state being clearly resolved. Integration of the signals shows that 22 and 10% of the total copper is paramagnetic in the oxidised and reduced forms, respectively.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…19 An optically monitored equilibrium redox titration of the anaerobically prepared form of the enzyme showed that, in the absence of substrate, two electrons are transferred, each in a Nernstian process at +260 mV and +60 mV, the former corresponding to the addition of one electron to Cu A and, the latter, of one electron to Cu Z . 19 The enzyme can be prepared with each monomer in a fully oxidized, one-electron reduced (in which only Cu A is reduced), 20 The steady state activities towards N 2 O reduction of all these forms of the enzyme, when assayed with HH cytochrome c are similar at 0.034 U mg −1 . 14 However, use of the artificial electron donors, benzyl viologen and methyl viologen rather than the natural electron donors, in steadystate kinetic measurements results in increased activity of the enzyme to ca.…”
Section: T H I S J O U R N a L I S © T H E R O Y A L S O C I E T Y O mentioning
confidence: 99%
“…Since N 2 OR was first isolated from Pseudomonas stutzeri (formerly Pseudomonas perfectomarina) [28,29], it has been purified and characterized from other bacterial sources, such as Rhodobacter capsulatus (formerly Rhodopseudomonas capsulate) [30], Rhodobacter sphaeroides f. sp. denitrificans [31], Paracoccus denitrificans [32], Wolinella succinogenes [33], Flexibacter canadensis [34], Achromobacter cycloclastes [35], Pseudomonas aeruginosa [36], Paracoccus pantotrophus (formerly Thiosphaera pantotropha) [37], Thiobacillus denitrificans [38], Alcaligenes xylosoxidans [39,40], Pseudomonas nautica (renamed Marinobacter hydrocarbonoclausticus) [41], and more recently Hyphomicrobium denitrificans [42].…”
Section: Introductionmentioning
confidence: 99%